The notion of true faith in the poetic work of Prudentius: an analysis of the poem Apotheosis - Ana Teresa Marques Gonçalves (Heródoto, 2018)
At a time when one was seeking to consolidate Christian principles, prompting converts to have their own social practices, differentiated from those exercised by Gentiles, Prudentius offers a work called Apotheosis, in which he advocates a uniqueness of identity for Christians, which would make them identify the errors of beliefs indicated as heretical. Presenting poetically the major departures in faith, the author seeks to provide a notion of true faith in which converts could begin to develop the right paths for those who wished to follow Christianity and obtain an eternal life after death. It is a proselytising work, which sought to provide exercise canons for the Christian faith for those already converted and for Gentiles in the process of conversion.